2001
DOI: 10.1016/s0092-8674(01)00378-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein-2 Negatively Regulates Insulin Secretion and Is a Major Link between Obesity, β Cell Dysfunction, and Type 2 Diabetes

Abstract: beta cells sense glucose through its metabolism and the resulting increase in ATP, which subsequently stimulates insulin secretion. Uncoupling protein-2 (UCP2) mediates mitochondrial proton leak, decreasing ATP production. In the present study, we assessed UCP2's role in regulating insulin secretion. UCP2-deficient mice had higher islet ATP levels and increased glucose-stimulated insulin secretion, establishing that UCP2 negatively regulates insulin secretion. Of pathophysiologic significance, UCP2 was markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
771
10
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 857 publications
(867 citation statements)
references
References 52 publications
62
771
10
8
Order By: Relevance
“…In humans, some, but not all (Klannemark et al 1998), studies showed that UCP2 gene variants are implicated in diabetes, obesity, and fat metabolism (Zhang et al 2001) and are strongly linked to resting energy expenditure (Astrup et al 1999;Buemann et al 2001;Walder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, some, but not all (Klannemark et al 1998), studies showed that UCP2 gene variants are implicated in diabetes, obesity, and fat metabolism (Zhang et al 2001) and are strongly linked to resting energy expenditure (Astrup et al 1999;Buemann et al 2001;Walder et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both fast and caloric restriction increase the activity of UCP2 an inner mitochondrial membrane protein involved in the regulation of energy metabolism (Andrews 2010;Zhang et al 2001), mitochondrial biogenesis, fatty acid oxidation, substrate utilization and ROS elimination, providing neuroprotective and anti-aging effects (Conti et al 2006;Bechmann et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These mice have increased circulating insulin concentrations concomitant with reduced blood glucose in the fed state. Insulin secretion from glucose-stimulated isolated islets is also significantly enhanced and the ATP:ADP ratio is increased [111]. Conversely, overexpression of UCP2 in ZDF rat islets shows an increase in preproinsulin mRNA together with an improvement in GSIS [112].…”
Section: Fuel Metabolismmentioning
confidence: 96%
“…Rats fed a high fat diet for 3 weeks [109] and hyperlipidaemic, diabetic ob/ob mice [111] have increased islet UCP2 mRNA expression. Such lipid-associated upregulation could contribute to the development of insulin insufficiency and subsequent hyperglycaemia.…”
Section: Relation Of Ucp2 With Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation